THE QUALITIES OF FORENSIC STYLISTICS ENFOLDED IN SUICIDE NOTES - Siti Maharani; Rahmadsyah Rangkuti; Manugeren Manugeren (Universitas Negeri Medan, 2022)
Abstract Suicide notes are messages left by people who have committed suicide or plan to commit suicide. These written messages express the victims' thoughts and emotions that they could not assert since they were alive. As a result, the purpose of this descriptive study is to investigate the characteristics of linguistic features of suicide notes written by eleven well-known male individuals. The method used in this study is qualitative content analysis. The data came from suicide notes written by eleven well-known males. These notes were available online. The researchers read, categorized, and explained the data consisting of five linguistic features of suicide notes: clear reasoning, expressing emotion, structure text, grammar, and punctuation. The findings revealed that all of the linguistic items were present in the suicide notes of very well individuals. The characteristics of clear reasoning were the most frequently observed because it informs readers of the victims' point of view about the reasons that led to their suicide. While the absence of hesitation and form of location occurred on an odd event. Finally, the findings of this study may aid future research into the study of suicide notes in forensic linguistics, the use of linguistics in data analysis, or legal issues Keywords :suicide notes; characteristics; linguistic features; forensic linguistics